Analisis Modul Ajar Berbasis Pendidikan Karakter - Ahmad Saefu; Hanandita Dewi Marselinda; Nurina Setiawati; Samsul Musafa; Wulan Nafisatul Munawaroh; Siti Fatimah; Imam Subarkah (IAINU Kebumen, 2023)
Teaching modules are learning tools arranged by teachers to plan the learning process. The research aims to analyze teaching modules based on character education. The subjects in this study were class teachers at Banioro Elementary School, Karangsambung, Kebumen. The type of method used in this study is a qualitative method with data collection techniques used namely observation, interviews, and documentation. The data analysis process includes several stages, namely data reduction, then presenting the data to draw conclusions. Based on the results of this study, it can be concluded that the teaching modules developed by teachers contain several characters, including religion, literacy, critical thinking, collaboration, communication, creativity, and tolerance. Keywords: Teaching Module, Character Education